A generic homonym concerning chordeumatid millipedes (Arthropoda: Diplopoda) and ophellid worms (Annelida: Polycheata) - Brewer, Michael S.; Sierwald, Petra; Bond, Jason E. (Zootaxa, 2011)
The Diplopoda is a megadiverse group, comprising > 12,000 nominal species with an estimate of total global diversity as high as 80,000 (Adis & Harvey 2000; Hoffman 1980; Sierwald & Bond 2007). An electronic, searchable database of the Diplopoda is currently being compiled at the Field Museum of Natural History in Chicago, IL. This catalog, and others like it, provides the basis and quality assurance for future taxonomic works and larger initiatives like the Encyclopedia of Life (EOL). The catalog will contain the most up-to-date and researched account of millipede diversity and literature records ever compiled and will be made accessible online.